CERPEN âMARAKIBU ASY-SYAMSIâ DALAM KUMPULAN CERPEN LAILATU AZ-ZIFAF KARYA TAUFIQ AL-HAKIM: ANALISIS STRUKTURAL ROBERT STANTON - , M. KHOIRUR ROZIKIN ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The short story which the title âMara>kibu asy-Syamsiâ in anthology of short story Lailatu az-Zifa>f is one of the masterpiece from Egypt writer, Taufi>q al-H}aki>m. The purpose from this study is to identify the intrinsic elements that sets this short story with Stantonâs structural analysis. Intrinsic elements in this study consist of the theme, the fact, and the facilities of story. The fact of story consists of the figure, the characterizations, the plot, and the setting themes. As for the facilities of story consists of the title, the point of view, and the symbolism. The elements was identified an d also described, so that it can be determined relationship between the elements to get the unity meaning intact. The result of this study show that theme of story âMara>kibu asy-Syamsiâ is struggle to against the arrogance to get admission of truth. As fo r the figure of this story consists of main and additional figures. Main figure of this story is carver and the additional figures are boat builders, pastor, ladies, empress, Firâaun, rabble and fisherman. This story uses the progressive plot and cover the stage of situation, appeared conflict, increasing conflict, climax, and completion stage. The setting themes of story is palace. The title of the story is refer to symbol story. This story is narrated with viewpoint not limited third person. Each element be related one of others, so that it produces unity meaning intact.